Non-perturbative Renormalization Group Approach to Some Out-of-Equilibrium Systems : Diffusive Epidemic Process and Fully Developed Turbulence /: Diffusive Epidemic Process and Fully Developed Turbulence. (2020) - Tarpin, Malo
No abstract available